The Meanings of Single-Letter Particles in the Book Ṣarf al-ʿInāyah fī Kashf al-Kifāyah by al-Baytūshī (d. 1221 AH). (Raparin Journal of Humanities (RJH), 2026)
This study inspects the syntactic and semantic orientation of the Quranic quotation in monogram, in the book "Sarf al-Inayah fi Kashf al-Kifayah" by the Kurdish scholar Abdullah al-Baytushi (d. 1221 AH). This is the second explanation on his poem "Kifayat al-Ma'ani fi Huruf al-Ma'ani". It addresses to focus on and explain the letters of meaning in grammar. In his clarification of the letters of meaning , he compromised poetic verses he composed himself, evidence of several grammatical matters related to the meanings of the letters. Al-Baytoushi’s technique in explanation is distinguished by analytical precision and dependence on the speech of grammarians who came before him. Al-Baytoushi relied in his book on authentic, reliable sources, from the Qur’an, Hadeeth, and poetry. He mentions his unique opinion , the opinions he preferred, the raised objections , and the corrections . He adopted the method of selection and preference without bias toward among the schools concerning explaining the meanings of the connotations of letters according to the alphabetical sequence, and adherence to monogram, double, triple, quadruple, and quintuple letters with guidance in syntactic analysis. His book shows his efforts to simplify complex syntactic issues for students, via methodological explanations, illustrative examples, and subjection to the scholars’ opinion and discussing objectively. The research focused on the Qur’anic evidence cited by Al-Baytoushi in his book for the meanings of monograms and explaining the letters, cited by many of Qur’anic verses , we’ll devote to the grammatical and semantic explanation. We’ll discuss the monograms, that their structure consists of one letter, depending on the descriptive analytical method, for reaching the result of this analysis.